Ceramic powder and method for producing ceramic powder

The ceramic powder with a surface-supported transition metal film addresses the issues of agglomeration and high aid usage in existing methods, enabling efficient, high-density sintering at lower temperatures with maintained material properties.

JP2025054526APending Publication Date: 2025-04-08NITERRA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023163601
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing ceramic manufacturing techniques require large amounts of sintering aids that impair mechanical strength, thermal conductivity, and electrical properties, and nanoparticles used as aids agglomerate and are expensive.

Method used

A ceramic powder with a thin film of transition metal or compound on its surface acts as a sintering aid, allowing for uniform dispersion and low-temperature sintering without significantly impacting the base material's properties.

Benefits of technology

The ceramic powder achieves high-density sintering at lower temperatures with improved mechanical and electrical properties by using a small amount of uniformly dispersed transition metal as a sintering aid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054526000001_ABST
    Figure 2025054526000001_ABST
Patent Text Reader

Abstract

To provide a powder material capable of reducing the addition amount of sintering aid and dispersing components in the sintering aid when used as a material for a sintered body.SOLUTION: A ceramic powder has a thin film supported on its surface, the thin film containing at least one of a transition metal and a transition metal compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ceramic powders and methods for making ceramic powders. [Background technology]

[0002] There are known products using ceramic materials obtained by mixing raw ceramic powder with powders of metal oxides, carbonates, or the like, and then firing the mixture (see, for example, Patent Documents 1 and 2). The alumina multilayer wiring board described in Patent Document 2 is formed from a ceramic material obtained by mixing fine alumina powder with a particle size of 5 to 50 nm with an alkaline earth metal compound, and then sintering the mixture. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-156458 A [Patent Document 2] Japanese Patent Application Publication No. 8-148786 Summary of the Invention [Problem to be solved by the invention]

[0004] In the techniques described in Patent Documents 1 and 2, a large amount of sintering aid is added during mixing before firing, which may impair the mechanical strength, thermal conductivity, and electrical properties of the base material. In contrast, by using nanoparticles as sintering aids to be added to the mixed powder before sintering, it is expected that the base material particles can be covered even with a small amount of addition, and sintering properties can be improved. However, nanoparticles are very prone to agglomeration, making it difficult to disperse them uniformly, and are also expensive.

[0005] The present invention has been made to solve at least part of the above-mentioned problems, and aims to provide a powder material which, when used as a material for a sintered body, reduces the amount of sintering aid added during mixing and has dispersed sintering aid components. [Means for solving the problem]

[0006] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in the following forms.

[0007] (1) According to one aspect of the present invention, there is provided a ceramic powder having a thin film containing at least one of a transition metal and a transition metal compound supported on a surface of the ceramic powder.

[0008] According to this configuration, a thin film containing at least one of a transition metal and a transition metal compound that functions as a sintering aid is formed on the surface of the ceramic powder before it is mixed with the sintering aid. That is, the transition metal element is finely dispersed on the surface of the ceramic powder. As a result, when a sintered body of the ceramic powder of this configuration is manufactured, the transition metal component supported on the surface of the ceramic powder functions as a sintering aid. Therefore, even if the amount of the supported sintering aid is small, it is possible to sufficiently activate the surface of the base material, and sintering can be performed at a lower temperature than when an auxiliary powder is added.

[0009] (2) In the ceramic powder of the above embodiment, the transition metal element contained in the thin film may be Mn (manganese). According to this configuration, Mn is widely dispersed on the surface of the ceramic powder, and further, sintering can be performed at a low temperature.

[0010] (3) In the ceramic powder of the above form, the content of Mn element may be 5 wt % or less. According to this configuration, the content of Mn element covering the surface of the ceramic powder is not too high, so the properties of the base material are not impaired. Furthermore, even if the amount of sintering aid supported is small, sintering can be performed at a low temperature.

[0011] (4) According to another aspect of the present invention, there is provided a method for producing a ceramic powder, comprising: a kneading step of mixing a ceramic powder base material with a complex containing a transition metal element ion; and a degreasing step of degreasing the mixture of the base material and the complex. According to this configuration, a ceramic powder having at least one of a transition metal and a transition metal compound formed on the surface is manufactured as a material powder that is the basis of a sintered body. The manufactured ceramic powder is fired to manufacture a sintered body. By using the ceramic powder of this configuration as a material, the transition metal added as a complex functions as a uniformly dispersed sintering aid. Therefore, sintering can be performed even at a low temperature.

[0012] The present invention can be realized in various forms, for example, in the form of a ceramic powder, a ceramic material, a sintered body, a wiring board, a system including these, a method for producing a ceramic powder, a method for producing a ceramic material, and a system including these. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view of a ceramic powder according to an embodiment of the present invention. [Diagram 2] 1 is a flowchart of a method for producing a ceramic powder. [Diagram 3] FIG. 2 is an explanatory diagram of the relationship between the temperature of a sintered body and the firing shrinkage rate. [Figure 4] FIG. 2 is an explanatory diagram of an SEM image of the sintered body of the present embodiment. [Diagram 5] FIG. 2 is an explanatory diagram of an SEM image of the sintered body of Comparative Example 1. [Figure 6] FIG. 2 is an explanatory diagram of the relative density of the sintered bodies of Examples 1 to 7. [Figure 7] 5 is a flowchart of a method for producing a ceramic powder according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] First Embodiment FIG. 1 is a schematic cross-sectional view of a ceramic powder 1 according to an embodiment of the present invention. The ceramic powder 1 shown in FIG. 1 includes a base material 2, which is a ceramic material, alumina (Al2O3) powder, and a thin film 3 supported on the surface of the base material 2. In this embodiment, the "thin film" also includes a film-like aggregate formed by an aggregate of a plurality of particles of Mn, which is a transition metal element, or a metal compound containing Mn. In this embodiment, the content of Mn element in the ceramic powder 1 is 5 wt% or less. The ceramic powder 1 is used as a material powder for electronic component packages, substrates for semiconductor manufacturing equipment, wireless communication module substrates, and substrates for control circuits.

[0015] FIG. 2 is a flow chart of a method for producing the ceramic powder 1. In the production flow shown in FIG. 2, first, alumina powder as the base material 2, a binder, a solvent, and a complex containing Mn element are prepared (step S1). The complex containing Mn element functions as a sintering aid. Next, alumina powder other than the complex, a binder, and a solvent are combined and kneaded using a three-roll mill (step S2). When the base material 2 is alumina powder, kneading before mixing with the complex can suppress agglomeration of alumina. Note that when aggregation of the base material 2 is minor, step S2 can be omitted.

[0016] The complex is added to the kneaded mixture and further kneaded to obtain a paste (step S3). The process in step S3 corresponds to the kneading step. In order to evaporate the solvent contained in the paste, it is dried at 120°C for 12 hours (step S4). Next, a degreasing step is performed to degrease the powder, which is a mixture of the alumina powder and the complex after drying (step S5). The degreasing step is performed for 5 hours at 450°C, a temperature at which the binder and the organometallic complex decompose. By this step, nanoparticles of Mn oxide that function as an auxiliary agent are precipitated on the surface of the alumina powder, which is the base material 2, and a ceramic powder 1 in which a thin film 3 is supported on the surface of the base material 2 is produced.

[0017] The produced ceramic powder 1 was subjected to chemical analysis and X-ray fluorescence analysis to confirm the component ratio between the base material 2 and the thin film 3 supported on the surface of the base material 2. As the chemical analysis, inductively coupled plasma atomic emission spectroscopy (ICP-AES) was performed. As sample pretreatment for ICP-AES, pressurized sulfuric acid treatment was performed. As the X-ray fluorescence analysis, the base material 2 was analyzed by the glass bead method (measurement diameter 30 mm) using a fluorescence spectrometer ZSX Peimus2, and the component ratio between the base material 2 and the thin film 3 supported on the surface of the base material 2 was confirmed.

[0018] Next, the sintering behavior of the ceramic powder 1 of this embodiment was evaluated using a thermomechanical analyzer (TMA). FIG. 3 is an explanatory diagram of the relationship between the sintering temperature and the shrinkage rate due to sintering. FIG. 3 shows the change in shrinkage with the change in sintering temperature. In FIG. 3, the change in sintering shrinkage of this embodiment is shown by a solid curve C1, the change in sintering shrinkage of Comparative Example 1 is shown by a dashed curve C2, and the change in sintering shrinkage of Comparative Example 2 is shown by a dashed curve C3. Comparative Example 1 is a molded body manufactured by the same manufacturing method as this embodiment using alumina and Mn2O3 as materials. Comparative Example 2 is an alumina molded body. As shown in FIG. 3, the curve C1 representing the change in sintering shrinkage in the molded body of this embodiment shrinks at a lower temperature than Comparative Examples 1 and 2. That is, it can be seen that the molded body of this embodiment is sintered at a lower temperature than Comparative Examples 1 and 2. The TMA measurement was performed using a TMA400SA made by Netz Japan at a heating rate of 5° C. / min in air.

[0019] Fig. 4 is an explanatory diagram of a scanning electron microscope (SEM) image of a sintered body in which ceramic powder 1 was fired at 1200°C. Fig. 5 is an explanatory diagram of a cross-sectional SEM image of Comparative Example 1 fired at 1200°C. Comparing Fig. 4 and Fig. 5, the sintered body of this embodiment shown in Fig. 4 has fewer holes formed on the surface than Comparative Example 1. In other words, the sintered body of this embodiment fired at 1200°C is formed more densely than the sintered body of Comparative Example 1.

[0020] FIG. 6 is an explanatory diagram of the relative density of the sintered bodies of Examples 1 to 7 produced using the ceramic powder 1 of this embodiment. FIG. 6 shows the relative density of the sintered body that changes depending on the amount of Mn element added to the ceramic powder 1 and the firing temperature during sintering. As shown in FIG. 6, Examples 1 and 2 are sintered bodies that have an added amount of Mn element of 2.3 wt% and are fired at 1200 and 1300 ° C., respectively. Examples 3 to 5 are sintered bodies that have an added amount of Mn element of 0.8 wt% and are fired at 1200, 1300, and 1400 ° C., respectively. Example 6 is a sintered body that has an added amount of Mn element of 5.0 wt% and is fired at 1200 ° C., and Example 7 is a sintered body that has an added amount of Mn element of 0.3 wt% and is fired at 1400 ° C. 6, the relative densities of Examples 1 to 7, in which the sintering temperature is 1200° C. or higher, are 96.8% or higher, which are higher than the relative densities of Comparative Examples 1 and 2. Therefore, the sintered bodies of Examples 1 to 7 are formed denser than the sintered bodies of Comparative Examples 1 and 2.

[0021] As described above, the ceramic powder 1 of this embodiment includes the base material 2, which is a ceramic material, alumina (Al2O3) powder, and the thin film 3 supported on the surface of the base material 2. In this embodiment, the thin film 3 containing Mn, which functions as a sintering aid, is formed on the surface of the ceramic powder 1. That is, the transition metal element is finely dispersed on the surface of the ceramic powder 1. As a result, when a sintered body of the ceramic powder 1 of this embodiment is manufactured, the Mn component supported on the surface of the ceramic powder 1 functions as a uniformly dispersed sintering aid. Therefore, even if the amount of the supported sintering aid is small, the ceramic powder 1 is sintered even at a low temperature (for example, 1200°C (Examples 1, 3, and 6)). In addition, Mn, which functions as a sintering aid, is well dispersed in the sintered body.

[0022] In this embodiment, the content of Mn element in the ceramic powder 1 is 5 wt % or less. With this configuration, the content of Mn element covering the surface of the ceramic powder 1 is not too large. Therefore, even if the amount of sintering aid supported is small, sintering can be performed at a low temperature without impairing the characteristics of the base material 2.

[0023] In the method for producing the ceramic powder 1 of this embodiment, the base material 2, which is alumina powder other than the complex, the binder, and the solvent are mixed and kneaded (step S2), and the complex is added to the mixture and further kneaded (step S3). After that, a degreasing step is performed to degrease the powder, which is the base material 2 after drying, which is a mixture of alumina powder and the complex (step S5), and the ceramic powder 1 is produced. In this embodiment, the ceramic powder 1 having a thin film 3 containing Mn formed on its surface is produced as a material powder that is the basis of the sintered body. The produced ceramic powder 1 is fired to produce a sintered body. By using the ceramic powder 1 as a material, the Mn added as a complex functions as a sintering aid that is uniformly dispersed. Therefore, the ceramic powder 1 is sintered even at a low temperature such as 1200°C, even if the amount of sintering aid supported by the ceramic powder 1 is small.

[0024] <Second embodiment> FIG. 7 is a flow chart of a method for producing a ceramic powder 1 according to the second embodiment. The ceramic powder produced in the second embodiment includes a base material, which is an alumina (Al2O3) powder, which is a ceramic material, and a thin film 3 formed of Mn supported on the surface of the base material. In the production flow shown in FIG. 7, first, alumina powder as a base material, a solvent, and a complex containing Mn element are prepared (step S11). Next, a kneading process is performed in which the solvent and base material are added to the complex and stirred (step S12). The paste after stirring is dried using an evaporator (step S13). The drying using the evaporator is performed under reduced pressure to prevent decomposition of the complex due to heating, and while stirring to prevent precipitation of the material powder. A degreasing process is performed to degrease the powder, which is a mixture of alumina powder and the complex after drying (step S14). The degreasing process is performed under the same conditions as in the first embodiment, and the ceramic powder 1 is produced.

[0025] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.

[0026] In the above first and second embodiments, the ceramic powder 1 in which Mn is supported as a thin film 3 on the surface of the base material 2 has been described. However, the ceramic powder can be modified to the extent that a thin film containing at least one of a transition metal and a transition metal compound is supported on the surface of the base material. For example, the thin film 3 supported on the surface of the base material 2 may be formed of a transition metal or a transition metal compound other than Mn. As the transition metal element other than Mn, for example, Mg, Co, Ni, Cu, and Zn that form spinel with alumina may be used, or a combination of these may be used. The thin film 3 does not have to cover the entire surface of the base material 2, and may only cover a part of it. The thin film 3 may be formed in a film shape on the surface of the base material 2, or may be a plurality of particles.

[0027] When the transition metal element contained in the ceramic powder 1 is Mn, the content of Mn may be more than 5 wt%. In order not to impair the characteristics of the base material, the content of the transition metal element contained in the ceramic powder 1 is preferably 5 wt% or less. In addition, as shown in Fig. 6, in order to improve the relative density, the content is preferably 2.3 wt% or less, and more preferably 0.8 wt% or less.

[0028] The method for producing the ceramic powder 1 shown in Figures 2 and 7 is an example, and can be modified to the extent that it includes a kneading step of mixing the ceramic powder with a complex containing a transition metal element ion, and a degreasing step of degreasing the mixture of the ceramic powder and the complex. For example, the drying of the mixture and the degreasing step may be performed in one step, or the dried powder may be molded and then degreased. In the process of step S2 in the production flow of the first embodiment shown in Figure 2, the ceramic powder, binder, and solvent may be kneaded by a ball mill instead of a three-roll mill.

[0029] The type of complex containing a transition metal element is preferably a fatty acid salt from the viewpoint of coating properties and solubility, but the complex can be modified to a range that is soluble in organic solvents and water, such as nitrates, sulfates, and ammonium salts.

[0030] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate.

[0031] The present invention can also be realized in the following forms. [Application example 1] A ceramic powder comprising: A ceramic powder having a thin film containing at least one of a transition metal and a transition metal compound supported on a surface thereof. [Application example 2] The ceramic powder according to Application Example 1, The ceramic powder is characterized in that the transition metal element contained in the thin film is Mn (manganese). [Application example 3] The ceramic powder according to Application Example 2, A ceramic powder, characterized in that the content of Mn element is 5 wt% or less. [Application example 4] A method for producing a ceramic powder, comprising the steps of: A kneading step of mixing a ceramic powder base material with a complex containing transition metal element ions; a degreasing step of degreasing a mixture of the base material and the complex; A manufacturing method comprising: [Explanation of symbols]

[0032] 1. Ceramic powder 2…Base material 3. Thin film

Claims

1. A ceramic powder comprising: A ceramic powder having a thin film containing at least one of a transition metal and a transition metal compound supported on a surface thereof.

2. 2. The ceramic powder of claim 1 , The ceramic powder is characterized in that the transition metal element contained in the thin film is Mn (manganese).

3. 3. The ceramic powder according to claim 2, A ceramic powder, characterized in that the content of Mn element is 5 wt % or less.

4. A method for producing a ceramic powder, comprising the steps of: A kneading step of mixing a ceramic powder base material with a complex containing transition metal element ions; a degreasing step of degreasing a mixture of the base material and the complex; A manufacturing method comprising:

Citation Information

Patent Citations

  • Alumina multilayer printed circuit board, manufacturing method thereof and manufacturing method of alumina sintered product

    JP1996148786A

  • Wiring board and manufacturing method for it

    JP2001156458A